A Review on Effect of Nickel Doping on Solder Joint Reliability - Siti Rabiatull Aisha, Idris; Zetty Akhtar, Abd Malek; Hardinnawirda, Kahar (2015)
Currently, the demands for portable electronic gadgets such as Personal Digital Assistant, tablets and smart phone have increased due to its light weight and multifunctionality. But the major drawbacks of these portable devices are prone to accidental drops and may cause internal circuit board damage. When an electronic product drops on the ground, the impact force and deformation which is transferred internally to the print circuit board (PCB) can cause brittle fracture at the solder joint interface or by impact ±8.tigue in the solder materials. Thus, in order to further enhance the mechanical properties of the solder joints, doping an element such as such as rare earth, Bi, Sb, Fe, Co, Cr, :Mn, Ti, In, Ni, and Ge as alloying addition has been selected in previous researchers as one of those solutions. This paper summarizes the effect of Ni doping element on intermetallic compound (IMC) formation, interfacial reaction and solders joint reliability. These reviews should provide an important basis of understanding the development of lead-free solders with addition of alloying elements.